Comparison of the combustion characteristics of gasoline and gasoline–ethanol blend under gasoline compression ignition mode. Issue 1 (31st December 2022) - Ngo, Van Thanh; Nguyen, Truong Giang
Abstract: In this study, conventional gasoline with a RON of 95 and gasoline–ethanol blend (20% ethanol in volume [E20]) were experimentally compared in terms of combustion characteristics and performance. First, second injection timing (SOI2 ) was investigated to study combustion characteristics while maintaining the dilution level at 25%. In this part, two fuels with high octane numbers were used to investigate the influence of ethanol on combustion characteristics under gasoline compression ignition (GCI) mode. The in-cylinder pressure and heat-release rate (HRR) indicated that the fueling of the engine with E20 leads to the maximum peak pressure and easier position of maximum HRR in comparison with pure gasoline in all cases of the second injection. The main HRR curve of E20 moves closer to the top dead center (TDC) compared with that of gasoline. This HRR behavior indicates that the overall HRR of E20 is more compact than that of gasoline. Second, SOI2 was fixed at two cases of −6, −3 crank angle degree (CAD) after TDC (ATDC), charge dilution and boosted pressure were investigated to study the sensitivity of dilution on combustion characteristics with gasoline–ethanol blend fuel. The in-cylinder pressure and HRR indicated a two-stage combustion phenomenon for a low dilution ratio (from 0% to 15%) and a single stage with a peak at approximately 5–6 CAD ATDC at high dilution.